No Temporal Change Seen in High‐Frequency Waves Scattered Near the Core‐Mantle Boundary - Ruoyan Wang; John E. Vidale; Wei Wang (Geophysical Research Letters)
Abstract The core‐mantle boundary (CMB) and the outermost core are dynamic and heterogeneous regions with time‐dependent flows. We examine two seismic raypaths, diffracted P and PKP precursors—both replete with scattering, with precisely repeating earthquakes. These earthquakes, occurring in the South Sandwich Islands, were recorded on the Yellowknife array in Canada, the Alice Springs array in Australia, and the Eilson Array in United States for the past 30 years. In all the most resolved cases, five for diffracted P and 19 for PKP precursors, we observe 1–2 Hz scattered waves that exactly repeat within the resolution of our study for more than 10 s. Although the absence of observable changes is unsurprising, it imposes constraints on potential temporal variations near the CMB. This suggests that any dynamic processes in this region might either be too subtle to detect, even with high‐frequency waves, or occur on different timescales.